Parents-Teacher Collaboration in Building Akhlak Karimah with the Normative Re-Educative Strategy for Elementary School Students in Sungai Pinang Village South Kalimantan - Mila Hasanah; Dwi Putra Cahyo Ramadhan; Alya Annida; Nihayatur Rahilah; Nkmah Nikmah; Muhammad Junaidi; Ria Puspita Sari; Riyani Riyani (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Family and school are two elements that cannot be separated in overcoming the moral crisis that occurs in the Era of Globalization. Teachers build students' good morals while parents provide further guidance and supervision regarding their children's behaviour at home. Parents and teachers have a significant role in building children's morals. So, the collaboration of parents and teachers in building akhlak karimah is essential. This study aims to determine the collaboration of parents and teachers in building good morals with normative re-educative strategies for elementary school students in Sungai Pinang Village, South Kalimantan. Applying a qualitative descriptive research method with an ABCD approach, the stages in this method approach are discovery, dream, design, define, and destiny. The results of this assistance show that cooperation between teachers and parents is essential in shaping the good morals of children in Sungai Pinang. A persuasive approach by involving teachers and parents in guidance and examples of good behaviour to children is key to achieving the goal of building good morals in the younger generation in Sungai Pinang.